Localizing private social standards: Standard initiatives in Kenyan cut flowers - Lone Riisgaard (Danish Institute for International Studies (DIIS), 2008)
Since the mid-1990s a range of Southern social standard initiatives have emerged, including in the African horticultural industry. In this paper I analyse two Kenyan standard initiatives in the cut flower sector - a business initiative and a multistakeholder initiative. I investigate how inter-national social standard requirements are 'localized', and how standards are played in different ways by different stakeholders in order to gain influence and to further specific goals. The ana-lysis shows that when the standards are negotiated and performed, the power relations that exist both between local stakeholders and along the global value chain (GVC) for cut flowers are reflected and reproduced. The analysis further reveals a general tension between a focus on private social standards (PSSs) as a technical tool to achieve social compliance based on outcome standards, and a focus on PSSs as a means of enhancing the process through which workers claim their rights. This tension is clearly reflected in the fact that when the multistakeholder standard is endorsed by other local standard initiatives, it is to the exclusion of the multistake-holder institution and to the exclusion of the participatory auditing methodology - the main vehicle through which process rights are promoted. Placing the local standard initiatives in the context of GVC governance, this paper also illustrates how local standard initiatives can be seen as indirectly playing into the governance agenda of retail buyers, because local standards (particularly multistakeholder standards) offer better insurance against conflict and create necessary consensus and 'back-up' from critical voices, both locally and in buyer markets.
Keywords: 330; Zierpflanzenbau; Internationale Sozialstandards; Selbstverpflichtung; Kenia